THE IMPACT OF ENTERPRISE SOCIAL NETWORKS ON MANAGEMENT PROCESS IN THE CZECH REPUBLIC - Školudová, Jana (Varazdin Development and Entrepreneurship Agency, 2017)
The process of globalization affects economic consequences in business and management. Due to globalization, there are various key changes, especially the rapid development of information technology. Effective management and leadership involve creative problem solving, motivating employees and making sure the organization accomplishes goals. Managers addresses the issue of the significance and financial and non-financial benefits of information technology to business management. For manager thinking about investing in IT for the first time, picking the right technical tool for organization is not easy. Different platforms can cater for the needs of different kinds of businesses. Enterprise Social Network is one of many information tools. The aim of this paper is to provide an answer to the research question of the impact of Enterprise Social Networks on the management process. Research methodology is based on questionnaire survey in the Czech Republic. The research includes both sequential and parallel managerial functions. The determined hypothesis focuses managers' decision-making process. Whether corporate social network has an impact on the decision-making process managers is explored. The research results presented influence of the Enterprise Social Networks on the managerial functions. Research results show that Enterprise Social Networks are an increasingly common part of the modern workplace, and in cases, replacing intranets. The emergence of consumerized IT has lead employees to expect user-friendly systems that offer functionality. This paper discusses whether Enterprise Social Networks are becoming increasingly popular worldwide in enterprise / business.
VLIV PODNIKOVÝCH SOCIÁLNÍCH SÍTÍ NA MANAŽERSKÝ PROCES V ČESKÉ REPUBLICE
Keywords: information systems; enterprise social networks; functions of management; organizations; informační systémy; podnikové sociální sítě; manažerské funkce; podniky